Unifying non-commutative geometry with Casimir energy: A novel f(R) wormhole solution - N.S. Kavya; C.S. Varsha; L. Sudharani; V. Venkatesha (Nuclear Physics B)
A Casimir wormhole is a theoretical concept proposing the negative energy density, generated through the Casimir effect that could support the existence of a traversable wormhole. This article investigates the feasibility of a Casimir wormhole by unifying the Casimir effect and non-commutative geometry within the framework of f(R) gravity theory using Lorentzian distribution. In this study, we derive the shape function satisfying the throat condition and graphically verify all necessary conditions for a traversable wormhole by varying the gravitational mass μ. In addition to this we examine all the energy conditions and physical properties, to assess the wormhole's stability.